Weighted Composition Groups on the Little Bloch Space - S. B. Mose; J. O. Bonyo (Journal of Function Spaces)
Dedicated to Prof. Len Miller (PhD advisor to J. O. Bonyo) and Prof. Vivien Miller of Mississippi State University on their retirement